Prognostic Scoring for Chronic Kidney Disease Among Type 2 Diabetes Patients in Malaysia: A Review of the i-CKD Tool - Muhammad Hariz ‘Ammar Khebir; Tajul Rosli Razak; Muhammad Iqbal Abdul Hafidz; Nurhuda Ismail; Mohamad Rodi Isa (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Chronic kidney disease (CKD) is a major complication of type 2 diabetes and contributes significantly to morbidity and healthcare costs in Malaysia. Early recognition of individuals at risk is essential, yet current clinical prediction practices remain inconsistent and are not systematically informed by combined clinical and biochemical parameters. A structured prognostic score offers a systematic approach to support early risk stratification and timely intervention. Objective : This review aims to synthesize evidence on the development and validation of the i-CKD prognostic scoring tool designed to predict chronic kidney disease risk among patients with type 2 diabetes in Malaysia. Research Methods/ Implementation Methods : This review will explore the staged development process of the i-CKD score, including the identification of key predictive factors, development of the scoring model, and subsequent internal and external validation. The methodological evaluation will emphasize the selection of predictors and statistical assessment of model discrimination and reliability throughout each phase. Results : A prognostic scoring tool (i-CKD score) will be developed and undergo internal and external validation to determine its predictive performance. Conclusion/Lesson Learned : This review underscores the value of structured risk stratification in the early detection and management of chronic kidney disease. While various prognostic tools have been proposed, limitations in standardization, validation, and clinical integration persist. The i-CKD score has the potential to strengthen clinical decision-making by supporting earlier identification of high- risk individuals.